Productivity intervention and smallholder farmers: the case of Ghana’s Cocoa Abrabopa Program - Phillips, Frederick Odame (Kansas State University, 2014)
Despite the dependence of more than three-quarters of a million households depending on cocoa for their living in Ghana, the production segment of the cocoa industry is fraught with significant challenges manifesting as low farm productivity. Various intervention programs to help farmers improve productivity at the farm level have been used over the past few decades. One of such programs is the Cocoa Abrabopa Program (CAA), which uses an integrated approach where farmers are supplied inputs made up of fertilizer, pesticides and fungicides as well as provided training and extension support services. The inputs are provided on credit and the producers repay the cost of these inputs upon selling their crop. This study sought to assess the results of the CAA in enhancing the net profits of its members over time. It used survey data collected over five years from members of the CAA program. The study used an econometric model to evaluate the demographic and production characteristics of CAA members on their net profits. The results show that male members in the CAA program had higher net profits that their female counterparts, about GHS 237.32 more. For every year increase in the member’s age, the net income increased by GHS 6.46, which was statistically significant at the 10 percent level. The crux of the study – the effectiveness of the CAA program in enhancing performance – was supported by the results. Participants who were two years in the program posted GHS 591.13 more net profit than those who were in their first year. Those who were three year and four or more years posted respectively GHS 1,211.04 and GHS 18,752.29 than those in the first year. All these were statistically significant at the 1 percent level. Thus, the CAA program is producing what it is expected to produce – enhancing the net profits of its members and doing so in higher levels with the duration of membership. The study also found that having a bank account produced a higher effect on net profits than being male, posting GHS 296.13 more net profit than not having a bank account. The econometric model specified and estimated was significant and the variability in all the independent variables in the model explained about 46 percent of the variability in net profits. The study recommends that the CAA program incorporates helping all its members open bank accounts as part of its offerings. It also recommends working with policymakers and community leaders across its operational areas to encourage investments in the education of females and elimination of the tenural rights discrimination that frequently confronts females in agriculture. It also recommends that an increased effort be made to expand membership of the CAA program to all cocoa producers in Western South because of the significant benefit of the yield effect of the region on net profit of CAA members in the region.
Keywords: Cocoa Economics; Ghana; Farming system; Abrabopa; Cocoa production; Economics (0501); Economics, Agricultural (0503); Economics, Commerce-Business (0505)